1993
DOI: 10.2527/1993.7141032x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonfiber carbohydrate level and Aspergillus oryzae fermentation extract on intake, digestion, and milk production in lactating dairy cows

Abstract: Eight multiparous, ruminally cannulated Holstein cows averaging 40 d in milk and 575 kg BW at the start of trial were in a replicated 4 x 4 Latin square arrangement (28-d periods) to determine the effects of dietary nonfiber carbohydrate (NFC) level and Aspergillus oryzae fermentation extract (AO) on intake, milk production, and nutrient digestibility. Treatments were 42 or 35% NFC and 0 or 3 g of AO per day arranged as a 2 x 2 factorial. Diets formulated to contain 21% NDF from alfalfa silage (48.4% of ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…In the present study, NDF:NFC was 0.77, 1.01 and 1.07 for TMR1, 2 and 3 of different forage combinations, and lower acetate and greater propionate in the rumen were found for TMR1 with forage combinations of alfalfa hay, Chinese wild ryegrass hay and whole corn silage than those for TMR2 and TMR3 containing corn stover and rice straw, respectively. The results were consistent with a previous study which showed that lower acetate and greater propionate occurred in the rumen of ruminants fed lower NDF:NFC diet than those with greater NDF:NFC diet (Granja-Salcedo et al, 2016;Sievert & Shaver, 1993). Differences among TMR1-3 in the present study were observed in volatile fatty acid content, suggesting that TFA (total fatty acid in milk) = C8:0 + C10:0 + C12:0 + C14:0 + C14:1 cis-9 + C16:0 + C16:1 cis-9 + C18:0 + C18:1 trans-11 + C18:1 cis-9 + C18:2n-6 + C18:3n-3 + C20:0 + C20:3n-6 + C20:4n-6 + C22:0; UFA (unsaturated fatty acid) = C14:1 cis-9 + C16:1 cis-9 + C18:1 trans-11 + C18:1 cis-9 + C18:2n-6 + C18:3n-3 + C20:3n-6 + C20:4n-6; SFA (saturated fatty acid) = C8:0 + C10:0 + C12:0 + C14:0 + C16:0 + C18:0 + C20:0 + C22:0; SEM, standard error of least square means; DMI, dry matter intake.…”
Section: Effect Of Tmrs With Different Forage Combinations On Rumensupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, NDF:NFC was 0.77, 1.01 and 1.07 for TMR1, 2 and 3 of different forage combinations, and lower acetate and greater propionate in the rumen were found for TMR1 with forage combinations of alfalfa hay, Chinese wild ryegrass hay and whole corn silage than those for TMR2 and TMR3 containing corn stover and rice straw, respectively. The results were consistent with a previous study which showed that lower acetate and greater propionate occurred in the rumen of ruminants fed lower NDF:NFC diet than those with greater NDF:NFC diet (Granja-Salcedo et al, 2016;Sievert & Shaver, 1993). Differences among TMR1-3 in the present study were observed in volatile fatty acid content, suggesting that TFA (total fatty acid in milk) = C8:0 + C10:0 + C12:0 + C14:0 + C14:1 cis-9 + C16:0 + C16:1 cis-9 + C18:0 + C18:1 trans-11 + C18:1 cis-9 + C18:2n-6 + C18:3n-3 + C20:0 + C20:3n-6 + C20:4n-6 + C22:0; UFA (unsaturated fatty acid) = C14:1 cis-9 + C16:1 cis-9 + C18:1 trans-11 + C18:1 cis-9 + C18:2n-6 + C18:3n-3 + C20:3n-6 + C20:4n-6; SFA (saturated fatty acid) = C8:0 + C10:0 + C12:0 + C14:0 + C16:0 + C18:0 + C20:0 + C22:0; SEM, standard error of least square means; DMI, dry matter intake.…”
Section: Effect Of Tmrs With Different Forage Combinations On Rumensupporting
confidence: 93%
“…In the present study, NDF:NFC was 0.77, 1.01 and 1.07 for TMR1, 2 and 3 of different forage combinations, and lower acetate and greater propionate in the rumen were found for TMR1 with forage combinations of alfalfa hay, Chinese wild ryegrass hay and whole corn silage than those for TMR2 and TMR3 containing corn stover and rice straw, respectively. The results were consistent with a previous study which showed that lower acetate and greater propionate occurred in the rumen of ruminants fed lower NDF:NFC diet than those with greater NDF:NFC diet (Granja‐Salcedo et al., ; Sievert & Shaver, ). Differences among TMR1–3 in the present study were observed in volatile fatty acid content, suggesting that even and odd chain volatile fatty acid contents in the rumen fluid depended on the different forage combinations under the same ratio of concentrate to forage in TMRs.…”
Section: Discussionmentioning
confidence: 99%
“…Fondevila et al (1990) found that AO stimulated the rate but not the extent of fiber digestion in the rumen. As with the increase in microbial protein synthesis, other studies have found no effect of AO on fiber degradation in the rumen (Firkins et aI., 1990;Sievert and Shaver, 1993), and Beharka and Nagaraja (1993) reported that the ability of AO to stimulate fiber degradation in vitro was dependent on the forage used. As with the increase in microbial protein synthesis, other studies have found no effect of AO on fiber degradation in the rumen (Firkins et aI., 1990;Sievert and Shaver, 1993), and Beharka and Nagaraja (1993) reported that the ability of AO to stimulate fiber degradation in vitro was dependent on the forage used.…”
Section: Microbial Feed Additives and Enzymesmentioning
confidence: 96%
“…Cows in Square 1 had previously been ruminally cannulated. The cannulation protocol was as described by Sievert and Shaver (1993). Treatments were arranged as a 2 x 2 factorial with type of corn endosperm (su-Bn2 or dent) and level of forage in ration DM (60% [high] or 45% [low] first-cut alfalfa silage) as main effects.…”
Section: Methodsmentioning
confidence: 99%
“…Volatile fatty acid concentrations were determined using GLC (Varian 2100, Sunnyvale, CA) with GP 10% SP-1200/1% H3PO4 on 80/100 Chromasorb W AW column packing (Supelco) and corrected for recovery of the internal standard (2-ethyl butyrate). Samples stored for NH3 determination were analyzed by a modification of the method of Chaney and Marbach (1962) as described by Sievert and Shaver (1993).…”
Section: Methodsmentioning
confidence: 99%